Increasing Reading Fluency in Young Adult Readers Using Audiobooks - Britta Padberg-Schmitt (CLELEjournal, 2020)
Britta Padberg-Schmitt investigates ways in which the reading process and reading fluency in foreign language learners can be facilitated with the support of audiobooks. She shows how the support provided by an audiobook can inspire a hesitant reader to learn how to love to read.